Transanal total mesorectal excision for rectal cancer: a review - Mizrahi, Ido; Sands, Dana R. (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (September 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
Low anterior resection (LAR) with total mesorectal excision (TME) can present a technical challenge in patients with middle or lower third rectal tumors. The challenge increases in obese male patients, those with a narrow pelvis, and following neo-adjuvant chemo-radiation. These factors may hamper the quality of the TME specimen, increase laparoscopic to open conversion rates, consequently influence oncological outcomes, and decrease the rate of reconstructive surgery. Transanal TME (taTME) was developed to overcome the above-mentioned technical difficulties through enhanced visualization of the dissection planes in the distal most difficult portion of the TME procedure. The transanal approach may fa-cilitate a clearer distal and circumferential resection margin (CRM), offer more patients sphincter-preserving surgery, and serve as a natural orifice extraction site of the specimen. Recent publications report an acceptable perioperative and short-term oncologic outcomes when comparing taTME to open or laparoscopic LAR. The aim of this review is to sum-marize the available current literature on taTME and to propose future perspective of training, quality control, and clinical research.